2017
DOI: 10.1021/acsnano.6b08227
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput Survey of Ordering Configurations in MXene Alloys Across Compositions and Temperatures

Abstract: 2D transition metal carbides and nitrides known as MXenes are gaining increasing attention. About 20 of them have been synthesized (more predicted) and their applications in fields ranging from energy storage and electromagnetic shielding to medicine are being explored. To facilitate the search for double-transition-metal MXenes, we explore the structure-stability relationship for 8 MXene alloy systems, namely, (VMo)C, (NbMo)C, (TaMo)C, (TiMo)C, (TiNb)C, (TiTa)C, (TiV)C, and (NbV)C with 0 ≤ x ≤ 1, using high-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
137
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 168 publications
(148 citation statements)
references
References 62 publications
(102 reference statements)
10
137
0
1
Order By: Relevance
“…Due to a large variety of transition metals and surface functionalities, MXenes' properties can be tuned by selecting combinations of transition metals, X elements, and controlling their surface chemistries. Close to 30 MXenes have been experimentally reported (marked with green color in Figure ), whereas many more are predicted to exist and have been studied theoretically (marked with black color in Figure ) . Given that close to 100 MAX phases have been made, not counting unlimited solid solutions and a number of ordered double transition metal structures, there are endless and quickly expanding opportunities for producing MXenes with desirable properties.…”
Section: Introductionmentioning
confidence: 99%
“…Due to a large variety of transition metals and surface functionalities, MXenes' properties can be tuned by selecting combinations of transition metals, X elements, and controlling their surface chemistries. Close to 30 MXenes have been experimentally reported (marked with green color in Figure ), whereas many more are predicted to exist and have been studied theoretically (marked with black color in Figure ) . Given that close to 100 MAX phases have been made, not counting unlimited solid solutions and a number of ordered double transition metal structures, there are endless and quickly expanding opportunities for producing MXenes with desirable properties.…”
Section: Introductionmentioning
confidence: 99%
“…More than a dozen MXenes have been reported to date, launching experimental and theoretical activity worldwide. [49][50][51][52][53][54][55][56][57][58] The distinguishing characteristics of MXenes, including unique morphologies, high electronic conductivities, and rich chemistries, have rendered them attractive in many applications, especially for energy storage. [59][60][61][62][63][64][65][66][67][68] As one typical representative among the MXene family, Ti 3 C 2 T x is a primary focus of many researchers because of its well-known etching conditions and the detailed theoretical and experimental studies on its physical and electrochemical properties, as clearly shown by the publication record ( Figure 1d).…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned in Sec. II B, similar hierarchical cluster selection rules have been used for CE 3,4,41,[43][44][45]56,57 . Compared to previous works, the combination of these rules with sparsity-driven regularization in our work leads to more robust ECIs.…”
Section: Discussionmentioning
confidence: 99%
“…Initially, CE was largely applied to binary alloys 2, [13][14][15][16][17][18][19][20][21][22][23][24][25][26] . Thereafter, it has been applied to more complex systems, including ternary to quinary alloys 5,6,12,[27][28][29] , semiconductors 7,30 , battery materials 31,32 , clathrates 33,34 , magnetic alloys [35][36][37] , and nanoscale alloys 3,4,11,[38][39][40][41][42] . In complex systems, the reduced symmetry increases the number of symmetrically distinct clusters, exacerbating the cluster selection problem.…”
Section: Introductionmentioning
confidence: 99%